Development of Electronic Modules with Culturally Responsive Teaching and Augmented Reality based on Jambi Culture for Mathematical Literacy - Deska, Salsabila Putri; Pasaribu, Feri Tiona; Gustiningsi, Tria; Nusantara, Duano Sapta (Faculty of Teacher Training and Education, 2025)
The purpose of this study is to develop and evaluate the feasibility and quality of an electronic module based on Culturally Responsive Teaching (CRT) and Augmented Reality (AR), incorporating Jambi culture to enhance students' mathematical literacy skills in the topic of similarity. This research adopts a Research and Development (R&D) approach using the ADDIE development model. The participants were 35 seventh-grade students from class VII G at SMP Negeri 6 Kota Jambi. The instruments used in this study included validation questionnaires, practicality questionnaires, and effectiveness questionnaires. The e-module was considered valid based on assessments by subject matter and design experts, obtaining a validity score of 86.25%, which falls into the “valid” category. This indicates that the e-module integrates similarity material with CRT components and contextual problems related to Jambi culture, along with AR features aligned with indicators of mathematical literacy. The practicality test, based on evaluations from both teachers and students, yielded a score of 85.97%, categorized as “very practical.” Additionally, the students’ n-gain score reached 79.04%, indicating the effectiveness of the e-module in improving mathematical literacy skills. These findings support the integration of local culture and AR technology in instructional material development, offering a practical and engaging approach for educators to promote mathematical literacy through contextualized learning experiences.